Keluarga Sebagai Tempat Pertama dan Utama Pendidikan Iman Anak - Hilario Didakus Nenga Nampar; Silpanus (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2018)
This study aims to determine the role of the family as the first and foremost place for children's faith education. Research uses a qualitative approach with descriptive methods. Data collection techniques used are observation, interview and documentation study techniques. The results of the study indicate that the family as the first and foremost place for children's faith education is this task rooted in the main vocation of Christian husband and wife. Faith education covers many aspects and one of them is faith education. Children's faith education is very important because it is very influential, not only for their faith and life in church but also for their future. Good faith education from parents helps children to have the right knowledge of life, weigh and ask questions about everything so they can make the right choices. True knowledge is born if children have a good attitude or religious and spiritual life.